Kepemimpinan Kepala Sekolah Dalam Mengembangkan Budaya Agama di SMK Telkom Sandhy Putra Malang - Hasanah, Siti Muawanatul (AL-WIJDÃN Journal of Islamic Education Studies, 2017)
This study aims to (1) describe the religious culture in SMK Telkom Sandhy Putra Malang. (2) describes the principal strategies in the development of religious culture in SMK Telkom Sandhy Putra Malang. (3) explain citizen support schools in developing a religious culture in SMK Telkom Sandhy Putra Malang. The results showed that (1) Being religious culture in SMK Telkom) include: (a) The addition of self-development learning the art of reading the Qur’an (SBA), (b) habituation sof miles and greetings attitudes, (c) Implementation of Friday congregational prayers, girl’s learning, (d) The use of the hijab (Islamic dress) on the day and month of Ramadan Friday, (e) Development of Islamic religious activities through the BDI (Islamic proselytizing agency), (f) warning the great days of Islam (PHBI). (2) the principal strategies in developing the religious culture include: (a). Program planning, (b) give an example to the citizens of the school, (c) share and support religious activities, (d) Conducting evaluations. (3) citizens support the school has done very well by showing their commitment. Sequentially (sequential) residents support the schools to the cultural development of religion as follows: the principal’s commitment, the commitment of teachers, student commitment, and the commitment of employees. Keywords: Principal Leadership, Religious Culture